Scholarly reading (and writing) and the power of impact factors: a study of distributed cognition and intellectual habits - Hillesund, Terje (Frontiers in Psychology, 2023)
Using observational interviews and introducing theories of embodied and distributed cognition, this study examines the scholarly reading and the intellectual habits of a group of social scientists. All participants were working at universities in task environments dominated by digital artifacts and technologies. The study found a strong connection between scholarly reading and the scholars’ writing processes and a further coupling to their digital publishing activity. In examining the participants’ print and online reading, it turned out that their reading was so tightly coupled to their writing that this entanglement had to be at the core of the analysis. For the participants, relevance for their writing and possibility of publication were intertwined aspects of their scholarly reading and of their online searches for literature. In the paper, scholarly reading and writing are analysed as cognitive processes that extend beyond brain and body and comprise of cognitive artifacts of texts and of their material bearers, such as printouts, digital displays, computers, and of the Internet. In the process of creating text – or reading and writing – brains, bodies, and artifacts are considered to be dynamically coupled in a distributed cognitive process. Based on interviews with a sample of academics, the paper analyses how their scholarly reading relates to the other elements in such an extended process and how they utilize the affordances of cognitive digital artifacts in their creative and intellectual endeavours.